Enhanced gravity wave activity in the mesosphere lower thermosphere region over Tirunelveli as a response to tropospheric convective event - Krishnapriya, K.; Sathishkumar, S.; Sridharan, S. (My University, 2023)
The recent upgrade of Medium-Frequency (MF) wind radar at Tirunelveli (8.7⁰N, 77.8⁰E) has improved the height and time resolution of the wind measurements, which are utilized in the present study to examine high frequency (in periods 20–60 min) gravity waves (GW) in the mesosphere and lower thermosphere (MLT) region. We observe, in addition to the dominant wave activity during equinox months, dominant episodes of high-frequency GW activities in the meridional winds during the times 31 May–4 June and 25–27 June 2019. Using the perturbation ellipse method, we infer the direction of propagation of the GW and it is found to be in the north–south plane. The GW activity in the MLT region exhibits anti-correlation with NOAA outgoing longwave radiation (OLR) and positive correlation with rainfall rates indicating the latent heat release due to tropical convection as the possible source of the GW. Besides, the presence of dynamical instability is inferred from the calculations using the radar wind and the spaceborne SABER (Sounding of Atmosphere using Broadband Emission Radiometry) temperature data suggesting a possible causality of convectively generated GWs dissipation.
Keywords: High frequency gravity waves; Tropical Convection; MF radar; SABER; ERA5; TRMM